2023
DOI: 10.1155/2023/2115335
|View full text |Cite
|
Sign up to set email alerts
|

Bryophyllum pinnatum and Improvement of Nocturia and Sleep Quality in Women: A Multicentre, Nonrandomised Prospective Trial

Abstract: Nocturia is a pathologic condition that significantly affects the quality of sleep. The aetiology of nocturia is multifactorial, and the evidence available on its management remains limited. Besides behavioural measures, validated pharmaceutical treatment options exist but are, however, associated with marked side effects. Prospective clinical studies with tablets prepared from the leaf press juice of the plant Bryophyllum pinnatum revealed a tendency towards reduction of micturition in patients with overactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In the case of the pilot study, a trend in reduction of micturition frequency and a positive trend for efficacy were apparent ( Betschart et al, 2013 ). In the before-after comparison, a reduction in nocturia and a beneficial effect on sleep quality were observed ( Mirzayeva et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of the pilot study, a trend in reduction of micturition frequency and a positive trend for efficacy were apparent ( Betschart et al, 2013 ). In the before-after comparison, a reduction in nocturia and a beneficial effect on sleep quality were observed ( Mirzayeva et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Also the treatment of pregnant wistar rats with B. pinnatum showed no toxicity at therapeutic levels and merely reduced glucose levels ( Hosomi et al, 2022 ). All clinical studies performed so far showed that treatment with B. pinnatum preparations can be considered as safe and well-tolerated, without severe adverse events and only occasional adverse events that included stomach-ache, diarrhea, and exanthema ( Betschart et al, 2013 ; Simões-Wüst et al, 2018 ; Mirzayeva et al, 2023 ). Gastrointestinal side effects upon treatment with the best-investigated preparations of B. pinnatum , namely, Bryophyllum 50% tablets, are most probably related to the contained lactose in patients with lactose intolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1970s, B. pinnatum preparations started to be used in the treatment of preterm labour in a German anthroposophic hospital [ 3 , 4 ]; they are now widely used in Switzerland in obstetrics and gynaecology [ 5 ]. Clinical studies have shown B. pinnatum to be effective in treating premature labour [ 6 ], hyperactive bladder [ 7 ], and nocturia [ 8 ]. These clinical effects are supported by data obtained using various in vitro models (see, e.g., [ 9 11 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Reports indicate that the leaves of the plant (Bryophyllum pinnatum) have strong medicinal value and are used both externally and internally [5]. Bryophyllum pinnatum is highly recommended in treatment of nocturia [14], bleeding disorders, piles and is suggested to be a good source of vitamin [15]. It is consumed with the believe that the plant helps to clean the bladder and also serves as a toxin remover in the intestines [16].…”
Section: Introductionmentioning
confidence: 99%